Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.4773318
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion luminescence, ferroelectrics and piezoelectrics of Er Doped SrBi4Ti4O15

Abstract: Er3+ doped SrBi4Ti4O15 (SBT) bismuth layered-structure ferroelectric ceramics were synthesized by the traditional solid-state method, and their upconversion photoluminescent (UC) properties were investigated as a function of Er3+ concentration and incident pump power. Green (555 nm) and red (670 nm) emission bands were obtained under 980 nm excitation at room temperature, which corresponded to the radiative transitions from 4S3/2, and 4F9/2 to 4I15/2, respectively. The emission color of the samples could be ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 75 publications
(86 reference statements)
0
18
0
1
Order By: Relevance
“…To improve the piezoelectric performance of SBT ceramics, the piezoelectric properties of metal oxides modified SBT ceramics have been investigated extensively. For example, the Dy-modified SBT (SBT-Dy) has a piezoelectric constant d 33 value of 17 pC/N [25], the Er-modified SBT (SBT-Er) shows a d 33 value of 16 pC/N [26], and the Ho-modified SBT presents a d 33 value of 15 pC/N [27]. These results revealed that the rare-earth oxides can enhance the piezoelectric properties of SBT ceramics.…”
Section: Introductionmentioning
confidence: 75%
“…To improve the piezoelectric performance of SBT ceramics, the piezoelectric properties of metal oxides modified SBT ceramics have been investigated extensively. For example, the Dy-modified SBT (SBT-Dy) has a piezoelectric constant d 33 value of 17 pC/N [25], the Er-modified SBT (SBT-Er) shows a d 33 value of 16 pC/N [26], and the Ho-modified SBT presents a d 33 value of 15 pC/N [27]. These results revealed that the rare-earth oxides can enhance the piezoelectric properties of SBT ceramics.…”
Section: Introductionmentioning
confidence: 75%
“…This result is consistent the ferroelectric properties of the above material. It can be seen that the piezoelectric constant (d 33 ) were increased in all the modified compounds in comparison with the pure SrBi 4 Ti 4 O 15 .…”
Section: Ferroelectric and Piezoelectric Propertiesmentioning
confidence: 88%
“…Higher concentration of Ba 2+ substitution may give the diffuse phase transition in this system. lower c-axis ratio shows better saturated hysteresis loop than that with higher c-axis ratio due to weak ferroelectricity or higher conductivity in bismuth layered ferroelectric along c-axis [33].…”
Section: Dielectric Studiesmentioning
confidence: 98%
See 2 more Smart Citations